Effectiveness of Zakat-based Poverty Alleviation Program - Ayub Miah (Center of Strategic Studies (PUSKAS) BAZNAS, 2021)
Under the market economy framework, different development models and approaches have been tested in Bangladesh for quite a few decades to alleviate poverty. However, evidence shows that these programs did not equally benefit all categories of the poor. In particular, some survey reports observed that micro-finance institutions have failed to reach the hardcore poor. A few studies reveal that microfinance has created debt cycles to pay the instalments of loan by making new loan from moneylenders in some cases. This paper explores some policy strategies for poverty alleviation, focusing on the effectiveness of Zakat-based programs. The Islamic approach to poverty alleviation is more comprehensive than the conventional one. The Center for Zakat Management (CZM) has adopted an integrated approach overwhelming the limitations of the conventional methods in implementing Zakat-based poverty alleviation programs. The impact assessment reports show that its livelihood projects have successfully empowered the poor by transferring equity capital and skill development and supporting education, creating access to healthcare services, ensuring safe water, hygiene sanitation, and promoting religious values raising social awareness. CZM’s approach seems to be very comprehensive, covering the basic needs of an ultra-poor household and their way forward. The CZM’s integrated livelihood program may be replicated in other countries as well for further assessment.